Children's literature in the classroom - Zbaracki, Matthew D. (Sage, 2024)
"Children's literature is a powerful resource that can inspire a young reader's lifetime love of reading, but how can you ensure that your literacy teaching uses this rich creative world to its fullest? This book gives pre-service primary teachers an in-depth guide to each major type of children's book, examining the form, structure and approach of each. From fairy tales and non-fiction to picture books and digital texts, learn what qualities underpin outstanding children's literature and how you can use this to inspire rewarding learning experiences in your classroom. Each chapter is full of key book recommendations to help you select excellent age-appropriate texts for your learners, an international focus across English-language publishing, covers key books from Australian, US and UK authors, includes a special focus on Australian indigenous children's literature, busts popular myths about children's literature to give you a deeper understanding of the form, and gives evaluation criteria for every genre, helping you to recognise the qualities of high quality books." -- Publisher's description.